2013
DOI: 10.1136/bmjopen-2013-003483
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation impact indices and their independent predictors: a systematic review

Abstract: ObjectivesTo (1) identify all available rehabilitation impact indices (RIIs) based on their mathematical formula, (2) assess the evidence for independent predictors of each RII and (3) propose a nomenclature system to harmonise the names of RIIs.DesignSystematic review.Data sourcesPubMed and references in primary articles.Study selectionFirst, we identified all available RII through preliminary literature review. Then, various names of the same formula were used to identify studies, limited to articles in Engl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
145
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(149 citation statements)
references
References 90 publications
2
145
0
2
Order By: Relevance
“…The demographic questionnaire collected important control variables whose fulfillment or higher values the literature has associated with decreases of patients' rehabilitation impact indices [24], which were our dependent variables. These control variables included: age, trial duration (LoT) and in the clinic (LoS), cognitive impairment (FIM C ), time delay from lesion onset to rehabilitation unit admission (admission delay), gender (female), and USN.…”
Section: Data Collectionmentioning
confidence: 99%
“…The demographic questionnaire collected important control variables whose fulfillment or higher values the literature has associated with decreases of patients' rehabilitation impact indices [24], which were our dependent variables. These control variables included: age, trial duration (LoT) and in the clinic (LoS), cognitive impairment (FIM C ), time delay from lesion onset to rehabilitation unit admission (admission delay), gender (female), and USN.…”
Section: Data Collectionmentioning
confidence: 99%
“…The FIM effectiveness is defined as FIM gain/(126 points-FIM scores at admission), while the mFIM effectiveness is defined as mFIM gain/(91 points-mFIM scores at admission) [19]. The denominator in the definition here is the maximum possible improvement in FIM score for a given patient, while the numerator is the actual improvement in FIM score; thus the FIM effectiveness is a value between 0 and 1 which measures the improvement actually achieved as a fraction of the maximum potential improvement possible [19,20].…”
Section: Relationship Between Fim At Admission and Fim Effectivenessmentioning
confidence: 99%
“…The FIM effectiveness is defined as FIM gain/(126 points-FIM scores at admission), while the mFIM effectiveness is defined as mFIM gain/(91 points-mFIM scores at admission) [19]. The denominator in the definition here is the maximum possible improvement in FIM score for a given patient, while the numerator is the actual improvement in FIM score; thus the FIM effectiveness is a value between 0 and 1 which measures the improvement actually achieved as a fraction of the maximum potential improvement possible [19,20]. Among "studies investigating the influence of various factors on ADL improvement, " FIM effectiveness has been used more frequently than FIM gain or FIM efficiency (63 studies using ADL effectiveness, compared to 7 studies using ADL gain and 16 studies using ADL efficiency) [19].…”
Section: Relationship Between Fim At Admission and Fim Effectivenessmentioning
confidence: 99%
“…Recent studies have shown that T-cells also have an impact on tissue damage [12][13][14][15][16][17][18][19][20]. Several studies have seen that an attenuation of the inflammatory process could be a possible way to widen the therapeutic window after the acute event [8,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Total scores range from 18 to 126 and indicate to what extent an individual is capable to reach independence in ADL. In our study we used the FIM effectiveness, calculated as (FIM at discharge-FIM on admission)/(126-FIM on admission) according to Koh and colleagues [20]. FIM effectiveness, which is independent from FIM on admission, has been used to compare patients with various degrees of disability severity.…”
Section: Introductionmentioning
confidence: 99%